Questions for Vocational Training in Hospitality and Tourism in Australia (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2020)
This paper outlines some of the dilemmas of turning graduates from vocational education and training courses into industry-ready employees.  It raises a number of questions that are ripe for action research with the context of the Boyer model of scholarship.